SUBDURAL BLOCK – A COMPLICATION OF EPIDURAL ANAESTHESIA A CASE REPORT - Iztok Potočnik; Lucija Oberauner (Zdravniški Vestnik, 2003)
Background. Epidural anaesthesia (EA) is a regional anaesthesia method that interrupts afferent nerve conduction. Epidural space (ES) is a space between internal leaf of a dura mater and spinal periosteum. The complications of regional anaesthesia are rare and are less common than those of general anaesthesia. The incidence of permanent neurological deficit is 0.03–0.1%. Subdural injection is a complication of epidural anaesthesia with an incidence of 0.82%. Subdural space is difficult to enter deliberately as arachnoidea is closely adherent to the overlying dura in most patients. Injection of the local anaesthetic solution into this space produces a high level of sensory and motor anaesthesia. Patients and methods. A case of 47-year-old female operated for cancer of the rectosigma is described. According to the kind of operation, a combined general and epidural anaesthesia was used. Despite proper insertion of a epidural catheter and recommended tests of its incorrect placement, the total spinal block developed. It is believed that a rare complication in the form of so-called subdural block occurred. Conclusions. Combined general and epidural anaesthesia is becoming widespread for major surgery and it is commonly used in developed countries. The purpose of this study was to warn on relatively rare complication of epidural anaesthesia. Only careful attention and a high index of suspicion for the development of the signs of subdural block will prevent complications.